FIGO 2023 staging system predicts not only survival outcome but also recurrence pattern in corpus-confined endometrial cancer patients - Hua-Hsi Wu; Hung-Tse Chou; Shih-Yao Lin; Chiung-Ru Lai; Yi-Jen Chen (Taiwanese Journal of Obstetrics & Gynecology)
Objective: Approximately 10–15 % of endometrial cancer patients with tumors confined to the uterus (FIGO 2009 stage I) demonstrate recurrence and the oncologic outcomes are highly related to recurrence patterns. This study aimed to verify whether the FIGO 2023 staging system could discriminate outcomes. Materials and methods: Between January 2010 and March 2019, 536 FIGO 2009 stage I patients were eligible for this retrospective cohort study. Patient characteristics and clinicopathological data were retrieved from electronic medical records. The patients were reclassified according to the FIGO 2023 staging criteria. Oncological outcomes included the recurrence rate, recurrence pattern, and overall survival. Results: Among the 536 eligible patients, the (sub)stage migration rate was 23.5 % from the FIGO 2009 to the FIGO 2023 stage system. FIGO 2023 staging system resulted in (sub)stage up-migration, mostly owing to aggressive histological types. A higher recurrence rate was detected in the FIGO 2023 stage II patients (12.3 %) compared to the stage I patients (6.9 %). In comparison to the FIGO 2023 stage I patients, the stage II patients had a higher distant recurrence rate (8.8 % vs. 2.6 %) and poorer overall survival (38.0 vs 69.0 months, p = 0.02). Conclusion: Patients who are upstaged are prone to worse oncological outcomes, including distant recurrence and mortality. Therefore, comprehensive adjuvant treatment strategies based on each FIGO 2023 substage are imperative.